Cultural Preservation and Innovation in the Era of Digital Visual Arts - Effendi, Harris (Indonesian Scientific Publication, 2025)
Digital transformation is redefining the landscape of visual arts, merging technological innovation with evolving cultural and aesthetic practices. This narrative review examines the integration of artificial intelligence, virtual reality, and augmented reality into visual arts, focusing on opportunities, challenges, and aesthetic transformations. Literature was gathered from databases such as Scopus, Google Scholar, IEEE Xplore, and Web of Science using targeted keywords, with peer-reviewed studies published in the last decade included based on relevance to digital art practices. Results reveal that emerging technologies significantly enhance creativity, audience engagement, and accessibility through immersive experiences, digital archives, and online exhibitions. However, challenges persist, including risks of artistic identity loss, ethical dilemmas in authorship and intellectual property, and disparities in technological access across regions. Systemic factors, including policy frameworks, cultural institutions, and education, critically shape how these technologies are adopted and perceived. Proposed solutions highlight blockchain authentication, digital literacy initiatives, and policy interventions to balance innovation with cultural preservation. Nonetheless, research gaps remain, particularly in addressing socio-cultural implications and long-term effects of digital tools on creativity and heritage. This review underscores the urgency of interdisciplinary strategies and global collaboration to ensure digital transformation enriches, rather than diminishes, cultural diversity and artistic integrity.